P028 The Nox A1 ambulatory system is reliable when self-applied. (7th October 2021) - Cuesta, R; Roebuck, T; Ho, S; Naughton, M; McDermott, E; VanBraak, E; Beranek, R; Davis, S; Spiteri, M; Dabscheck, E; Miller, B; Yu, C
Abstract: Background: Home Sleep Apnea Tests (HSAT) increases access to SDB diagnostic testing (Safadi, 2014). A previous study defined a reliable HSAT if: ≥4hours total recording time, an intelligible position signal and respiratory effort, airflow and oximetry for at least 80% of the night were recorded, however, admits no standardized criteria in the literature (Domingo, 2010). Aim: To test the reliability of a self-applied HSAT using the Nox-A1 ambulatory system (NOX Medical, Iceland). Method: Patients self-applied the HSAT guided by industry produced video and written instructions. Signals for the HSAT included; two electro-occulagrams (EOG), two sub-mental electromyograms (EMG), a single modified frontal encephalogram (EEG), a lead I ECG, single leg anterior tibialis EMG, chest and abdominal inductance respiratory effort, nasal pressure airflow, WristOx 2 3150 SpO2 (Nonin Medical, Inc., USA) and 3-D accelerometer and body position sensor. Analysed with ProFusion PSG 4 (Compumedics Limited, Australia) after importing data into Nexus. 33 consecutive studies were recorded during lock-down. Recording satisfactory if SpO2 signal and EEG present >80% of study, it was considered a failure if doctor requested test repeat. Results: 33 subjects, age 43.1 ± 13.7 years, BMI 27.4 ± 6.0 kg/m2, 66.6% male. 81.8% of studies satisfactory. 6% of studies needed a repeat in-lab PSG due to 1) loss of oximetry & EEG and 2) loss of EEG Discussion: 6% doctor request repeat in-lab PSG is comparable to a study (Lloberes, 2001) of partially self-applied HSAT. Demonstrated good reliability with this self-applied COVID-safe method of HSAT.